“Step-by-Step” Minimally Invasive Hemostatic Technique Using Intrauterine Double-Balloon Tamponade Combined with Uterine Isthmus Vertical Compression Suture for the Control of Placenta Accreta and Severe Atonic Hemorrhage during a Cesarean Section - Takahashi, Masaya; Takeda, Jun; Haneda, Sumie; Ishii, Sumire; Shinohara, Mitsuko; Yoshida, Emiko; Sato, Anna; Makino, Shintaro; Itakura, Atsuo (The Surgery Journal, 2021)
A sudden onset of postpartum hemorrhage (PPH) during a cesarean delivery requires urgent hemostasis procedures, such as the B-Lynch, Hayman, or double-vertical compression sutures, when bimanual compression, uterotonic agent administration, and intrauterine balloon tamponade had failed to achieve sufficient hemostasis. However, after invasive hemostatic procedures, postoperative complications, including subsequent synechiae and infection followed by ischemia, have been reported to occur even in successful cases. To avoid these complications, we devised and performed a minimally invasive combined technique based on a “step-by-step” minimally invasive hemostatic protocol for a case of placenta accreta and severe atonic hemorrhage during a cesarean delivery. A nullipara woman with a history of systemic lupus erythematosus and treatment with prednisolone and tacrolimus underwent a cesarean section because of a nonreassuring fetal status. Severe atonic hemorrhage and placenta accreta were observed which did not respond to bimanual compression and uterotonics. Because severe uterine atony and continuous bleeding from the placental attachment area were observed even with intrauterine balloon tamponade, vertical compression sutures were placed in the uterine isthmus. However, severe uterine atony and atonic bleeding from the uterine corpus persisted; thus, a second balloon was inserted into the uterine corpus. Hemostasis was accomplished with a combination of isthmus vertical compression sutures and double balloons which is a less-invasive approach than existing compression techniques. No complications related to these procedures were observed. This step-by-step minimally invasive hemostatic technique has the potential to control PPH with less complications, especially in immunocompromised patients.
Keywords: cesarean delivery; atonic hemorrhage; intrauterine double-balloon tamponade; vertical compression suture; minimally invasive hemostatic technique; surgical technique